HERO'S JOURNEY IN ALEXANDRA OLIVA'S NOVEL THE LAST ONE - Fandi Kurniawan (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2023)
This study analyzes the theme of heroism in the novel The Last One by Alexandra Oliva. The study will focus on the main character and her journey to survival. The writer applies a qualitative research method in writing this study. In the analysis, the writer applies the Monomyth Cycle/Hero's Journey theory proposed by Joseph Campbell to analyze the story. The study determined whether the main character was considered a hero. The finding shows that the main character of The Last One novel went through all the stages of the hero’s journey, which made her a hero character.